1997
DOI: 10.1007/s002770050261
|View full text |Cite
|
Sign up to set email alerts
|

Alternating mini-BEAM/ESHAP as salvage therapy for refractory non-Hodgkin's lymphomas

Abstract: Mini-BEAM and ESHAP are two non-cross-resistant salvage regimens that have been used separately in patients with lymphoma. The aim of the present study was to investigate the efficacy of the combination of these two regimens, administered in alternating cycles, as salvage therapy for refractory non-Hodgkin's lymphoma (NHL) patients. A total of 28 patients were included in the study: 14 patients were primary refractory, seven were partial responders, and seven were in relapse. The alternating cycles of mini-BEA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
0
8
1
Order By: Relevance
“…The most significant adverse prognostic factors for response in both the whole series and the R+ group were the presence of bulky disease, primary refractory disease, an aaIPI higher than 1 at the time of R-ESHAP, as well as the administration of fewer than three cycles of R-ESHAP. Moreover, the presence of primary refractory disease and high-risk aaIPI at the time of R-ESHAP were also independent adverse prognostic factors for survival, in accordance with reports from other authors, 9,13,14,[23][24][25][26] but in contrast to the data published by Kewalramani et al, 13 who observed that the addition of rituximab to the ICE regimen seemed to overcome the adverse effects of an unfavorable IPI score. The dismal outcome of patients with primary refractory disease or with an unfavorable aaIPI at the time of relapse underlines the need for the evaluation of alternative treatments.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Ncontrasting
confidence: 56%
See 1 more Smart Citation
“…The most significant adverse prognostic factors for response in both the whole series and the R+ group were the presence of bulky disease, primary refractory disease, an aaIPI higher than 1 at the time of R-ESHAP, as well as the administration of fewer than three cycles of R-ESHAP. Moreover, the presence of primary refractory disease and high-risk aaIPI at the time of R-ESHAP were also independent adverse prognostic factors for survival, in accordance with reports from other authors, 9,13,14,[23][24][25][26] but in contrast to the data published by Kewalramani et al, 13 who observed that the addition of rituximab to the ICE regimen seemed to overcome the adverse effects of an unfavorable IPI score. The dismal outcome of patients with primary refractory disease or with an unfavorable aaIPI at the time of relapse underlines the need for the evaluation of alternative treatments.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Ncontrasting
confidence: 56%
“…These regimens produce overall response rates of around 60%, and complete remission rates of 25% to 35%. [5][6][7][8][9] More effective salvage regimens are needed in order to maximize the number of patients in complete remission prior to ASCT.…”
Section: Introductionmentioning
confidence: 99%
“…12,17 In this trial we chose to increase the doses of the two most active compounds, doxorubicin and cyclophosphamide, in combination with etoposide, which has shown its efficacy both as first-line therapy and in relapsing NHL patients. 17,18 Doxorubicin dose was limited to The only toxic death observed in the trial occurred on the first day of the first course in a patient who developed fatal tumor lysis syndrome, at the first dose level. Furthermore this regimen was adequate for stem cell collection, since cytaphereses were successful in all patients due to receive intensification.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 20 patients who had received radiation therapy before transplant, 7 patients received involved field radiation therapy after chemotherapy for an early-stage disease, 11 patients received radiation therapy for bulky or residual disease after chemotherapy and 2 patients with mediastinal /kg). The median post transplant days of neutrophil recovery and platelet were 9 days (range, [8][9][10][11][12][13][14][15][16][17][18][19] and 11 days (range, 7-19), respectively.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…4 Salvage chemotherapy was effective in 60-70% of patients with refractory or relapsed DLBCL, but could cure no 410% of such patients. [5][6][7][8][9] High-dose chemotherapy followed by autologous hematopoietic SCT has been shown to be superior to salvage chemotherapy alone for patients with chemosensitive relapsed or refractory aggressive nonHodgkin's lymphoma. [10][11][12][13][14] BEAM, CY plus TBI (CY/TBI) and some other regimens have frequently been used as conditioning regimens for autologous hematopoietic SCT.…”
Section: Introductionmentioning
confidence: 99%